2016
DOI: 10.2147/tcrm.s80749
|View full text |Cite
|
Sign up to set email alerts
|

Methylnaltrexone for opioid-induced constipation: review and meta-analyses for objective plus subjective efficacy and safety outcomes

Abstract: IntroductionOpioid-induced constipation (OIC) is a frequent adverse event that impairs patients’ quality of life. This article evaluates the objective plus subjective efficacy and the safety of methylnaltrexone (MNTX) in OIC patients.MethodsRandomized controlled trials from a recent systematic review were included. In addition, a PubMed search was conducted for January 2014 to December 21, 2015. We included randomized controlled trials with adult OIC patients, MNTX as study drug, and OIC as primary outcome. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 40 publications
2
26
0
8
Order By: Relevance
“…In phase III studies, both substances have been shown to be highly effective and tolerable [30][31][32]; both drugs may be combined with all available opioid regimes irrespective of the choices of substance, medication routes, or dosing.…”
Section: Secretagoguesmentioning
confidence: 99%
“…In phase III studies, both substances have been shown to be highly effective and tolerable [30][31][32]; both drugs may be combined with all available opioid regimes irrespective of the choices of substance, medication routes, or dosing.…”
Section: Secretagoguesmentioning
confidence: 99%
“…Several previous reviews on the similar topic have been published [22][23][24][25][26][27][28][29]. Six of them evaluated the treatment of OIC with different pharmacological therapies, mainly μ opioid receptor antagonists, including methylnaltrexone [22][23][24][25][26][27].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Abhängig vom Dosierungsverhältnis vom jeweiligen Opioid-Agonist zu Antagonist bleibt allerdings bei intakter Leberfunktion eine systemische Antagonisierung des Agonisten weitestgehend aus und es resultiert eine fast ausschließlich periphere Antagonisierung an den μ-Rezeptoren. Der Einsatz von PAMORAs (peripherally acting μ-opioid receptor antagonist) kann unabhängig vom Dosierungsverhältnis des Agonisten zum Antago- Ähnliche Ergebnisse werden auch für den PAMORA Methylnaltrexon gesehen; dazu sei auf eine Zusammenfassung die Originalarbeiten in den aktuellen Übersichten von Sonu et al [27], sowie Siemens und Becker verwiesen [28]: So kann auch unter Methylnaltrexon gegenüber Placebo Signifikanz für die Beschleunigung der Darmperistaltik gezeigt werden, wobei Methylnaltrexon in einer Publikation 68 gegenüber 45 % Placebo erreichte (0,009). Der Parameter "rescue-free bowel movement" (RFBM) bzw.…”
Section: Diagnoseunclassified